Organising the business processes of a product servitised supply chain: a value perspective. Issue 5 (3rd April 2016) - He, Ting; Ho, William; Zhang, Yufeng; Dey, Prasanta Kumar
Abstract: This paper develops a structured method from the perspective of value to organise and optimise the business processes of a product servitised supply chain (PSSC). This method integrates the modelling tool of e 3 value with the associated value measurement, evaluation and analysis techniques. It enables visualisation, modelling and optimisation of the business processes of a PSSC. At the same time, the value co-creation and potential contribution to an organisation's profitability can also be enhanced. The findings not only facilitate organisations that are attempting to adopt servitisation by helping avert any paradox, but also help a servitised organisation to identify the key business processes and clarify their influences to supply chain operations.